Studi Kualitatif Keberadaan Penyakit Kusta di Desa Dendun Kecamatan Mantang Kabupaten Bintan - Harvensica Gunnara; Rian Yuliyana; Rinaldi Daswito; Ratna Juwita; Hendra Dhermawan Sitanggang (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2020)
Indonesia is in the third position in the world with the most leprosy sufferers after India and Brazil. Leprosy is commonly found in developing countries, as a result of the country's limited ability to provide adequate services in the fields of health, education, and socioeconomic welfare for the community. Dendun Village in Mantang District had the most cases of leprosy, 5 (five) cases in the Bintan Regency area in 2018. The study was used as a qualitative approach with a case study method. Content analysis was used in the analysis process of this research. Testing the results of research used source triangulation by cross-checking data with facts from other sources (informants) and triangulation methods by collecting data through in-depth interviews with informants and reviewing documents. The level of knowledge, negative stigma, adherence to treatment, history of contact with leprosy sufferers, and access to health services were important factors for the existence of leprosy in Dendun Village, Mantang District, Bintan Regency. Patients are expected to comply with the treatment program seriously to prevent transmission, cure, and recovery due to diseases carried out by the Bintan District Health Office and Mantang Puskesmas.